A theoretical study of particle coalescence criteria for inelastic collisions of wet particles. (2nd November 2021) - Wu, Dongling; Zhou, Ping; Wang, Geoff; Howes, Tony; Chen, Wei
Highlights: Dimensionless strain is introduced to characterize the deformation degree. Nonlinear explicit contact force model is proposed for wet particles with plastic deformation. Particle coalescence caused by surface energy and plastic deformation is identified. A modified coalescence criterion is proposed under combined effects of capillary and viscous force. Abstract: Individual wet particle collisions can significantly affect the macroscale behaviors of granular flow systems. The collision process between two wet particles consists of deformation and non-deformation stages. In each stage, a force model is required to describe the interactive mechanics. Forces vary in a fashion that the energy dissipates during the entire collision process, which further impacts the particle coalescence. In this study, the force model and energy dissipation mechanism at each collision stage are investigated. For the deformation stage, combined effects of adhesion and plastic deformation at the contact surface are considered. For the non-deformation stage, combined effects of capillary and viscous force are studied. Based on energy conservation, the particle coalescence criterion is characterized into three distinct types. The developed explicit expression for the contact force, restitution coefficient, and corresponding coalescence criteria can be further applied in modelling of wet granular flow systems.